Invasive shrubs modify rodent activity timing, revealing a consistent behavioral rule governing diel activity. (10th April 2019) - Guiden, Peter W; Orrock, John L
Abstract : Invasive plants create darker habitats where mice venture out earlier. Animals adjust the timing of their activity to maximize benefits (access to resources) and minimize costs (exposure to predators). The thick canopy of invasive shrubs blocks moonlight from reaching the forest floor, allowing nocturnal mice to forage earlier in the evening during seasons when leaves of invasive shrubs are out. These different patterns of activity arise because mice use a simple rule, based on nighttime illumination, to govern activity in both invaded and uninvaded habitats. Abstract: Animals adjust the timing of their activity to maximize benefits, such as access to resources, and minimize costs, such as exposure to predators. Despite many examples of invasive plants changing animal behavior, the potential for invasive plants to alter the timing of animal activity remains unexplored. In eastern North America, invasive shrubs might have particularly strong effects on animal activity timing during spring and fall, when many invasive shrubs retain their leaves long after native species' leaves senesce. We experimentally removed an invasive shrub (buckthorn, Rhamnus cathartica ) and monitored the activity timing of a ubiquitous small-mammal species (white-footed mouse, Peromyscus leucopus ) in spring, summer, and fall. We captured nearly 3 times as many P. leucopus in plots invaded by R. cathartica compared with plots with R. cathartica removed, and P. leucopus were captured 2 h earlier in invaded plots. Regardless of invasion treatment, P. leucopus appear to follow a common rule to set activity timing: P. leucopus were only active below a threshold of ground-level moonlight illuminance (0.038 lux). Diel and monthly lunar cycles play an important role in regulating small-mammal activity, but our data suggest that decreased light penetration dampens the influence of moonlight illuminance in habitats invaded by R. cathartica, allowing P. leucopus to remain active throughout the night. By changing the temporal niche of ubiquitous native animals, invasive shrubs may have unappreciated effects on many ecological interactions, including processes that alter community diversity and affect human health.